Kinematic Components of the Reach-to-Target Movement After Stroke for Focused Rehabilitation Interventions: Systematic Review and Meta-Analysis - Collins, Kathryn C.; Kennedy, Niamh C.; Clark, Allan; Pomeroy, Valerie M. (Frontiers in Neurology, 2018)
Background Better upper limb recovery after stroke could be achieved through tailoring rehabilitation interventions directly at movement deficits. Aim: to identify potential; targets for therapy by synthesizing findings of differences in kinematics and muscle activity between stroke survivors and healthy adults performing reach-to-target tasks. Methods A systematic review with identification of studies, data extraction, and potential risk of bias was completed independently by two reviewers. Online databases were searched from their inception to November 2017 to find studies of reach-to-target in people-with-stroke and healthy adults. Potential risk-of-bias was assessed using the Down’s and Black Tool. Synthesis was undertaken via: (a) meta-analysis of kinematic characteristics utilizing the standardized mean difference (SMD) [95% confidence intervals]; and (b), narrative synthesis of muscle activation. Results Forty-six studies met the review criteria but 14 had insufficient data for extraction. Consequently, 32 studies were included in the meta-analysis. Potential risk-of-bias was low for one study, unclear for 30, and high for one. Reach-to-target was investigated with 618 people-with-stroke and 429 healthy adults. The meta-analysis found, in all areas of workspace, that people-with-stroke had: greater movement times (seconds) e.g. SMD 2.57 [0.89, 4.25]; lower peak velocity (millimeters/second) e.g. SMD -1.76 [-2.29, -1.24]; greater trunk displacement (millimeters) e.g. SMD 1.42 [0.90, 1.93]; a more curved reach-path-ratio e.g. SMD 0.77 [0.32, 1.22] and reduced movement smoothness e.g. SMD 0.92 [0.32, 1.52]. In the ipsilateral and contralateral workspace, people-with-stroke exhibited: larger errors in target accuracy e.g. SMD 0.70 [0.39, 1.01]. In contralateral workspace, stroke survivors had: reduced elbow extension and shoulder flexion (degrees) e.g. elbow extension SMD -1.10 [-1.62, -0.58] and reduced shoulder flexion SMD -1.91 [-1.96, -0.42]. Narrative synthesis of muscle activation found that people-with-stroke, compared with healthy adults, exhibited: delayed muscle activation; reduced coherence between muscle pairs; and use of a greater percentage of muscle power. Conclusions This first-ever meta-analysis of the kinematic differences between people with stroke and healthy adults performing reach-to-target found statistically significant differences for 21 of the 26 comparisons. The differences identified and values provided are potential foci for tailored rehabilitation interventions to improve upper limb recovery after stroke.